PELUANG DAN TANTANGAN KURIKULUM PENDIDIKAN TINGGI ISLAM DI INDONESIA - Fauzan Akmal Firdaus (CV. ADIBA AISHA AMIRA, 2023)
The educational curriculum plays an important role in the process of implementing learning in an educational institution. The curriculum is considered important, because the heart of education is in the curriculum used. The good and bad of graduates (ouput) produced by an education is determined by the curriculum implemented at every level of education. Islamic Universities is one of the levels of education that plays a role in smartening the life of the nation. The cause of the lack of quality of Islamic higher education is influenced by the inconsistency of the curriculum applied so that it is necessary to make changes according to the instructions of the government. This study aims to find out the challenges and opportunities of the Islamic higher education curriculum in Indonesia. This study uses library study methods. The results of the study show that the challenges and opportunities of the Islamic higher education curriculum lie in developing a curriculum that is structured and designed in accordance with the development of the times, the needs of the community and graduate users, as well as the competence of educators who are sufficient in implementing the curriculum implemented.